Implementasi UU Pelindungan Pekerja Migran Indonesia terhadap Pelanggaran Penempatan ABK WNI di Sektor Perikanan yang Dilakukan oleh Orang Perorangan (Studi Kasus Putusan Nomor 929/Pid.Sus/2020/PN.Btm) - Alvin Daun; Muhammad Pasya Rulli (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This article analyzes violations of the placement of Indonesian ship crew (ABK WNI) in the fisheries sector committed by individuals as regulated in Article 69 of Law 18/2017 in Court Decision Number 929/Pid.Sus/2020/PN.Btm. The legal questions are: 1) How is the implementation of the Law on the Protection of Indonesian Migrant Workers on violations of the placement of fisheries crew members committed by individuals in Decision Number 929/Pid.Sus/2020/PN.Btm?; and 2) What are the procedures for the placement and protection of Indonesian Migrant Workers based on Indonesian laws and regulations? This article is a normative juridical type with a statutory approach and a case approach. The results of this study indicate that 1) The violation of placement of Indonesian crew members committed by PT MJM Abdi Baruna is a type of placement violation committed by individuals despite the status of a limited liability company because it does not have SIP3MI, SIP2MI, and SIUPPAK; and 2) Procedures for the placement and protection of Indonesian ship members in the fisheries sector carried out by crew agency business entities in details had been regulated in PP No. 22 of 2022, P2MI / BP2MI Permen No. 1 of 2025, and Minister of Transportation Regulation No. 59 of 2021.